Treatment for papillary thyroid microcarcinoma - Shi, Lan; Chen, Jun-hua; Wang, Shun-tao; Xiong, Yi-quan; Huang, Tao (Contemporary Oncology/Współczesna Onkologia, 2013)
Aim of the study: The treatment for papillary thyroid microcarcinoma (PTMC), which is a tumor measuring less than 1 cm, is still a subject of controversy. The aim of this study is to retrospectively evaluate the patients diagnosed with PTMC in terms of their clinical and histopathological features. Material and methods : A total of 153 consecutive patients with PTMC were treated, and their clinical and histopathological characteristics were reviewed. The tumor diameter was observed to range from 1.0 mm to 10 mm (mean of 5.8 mm). Histologically, 138 (90.2%) cases of classical papillary carcinoma and 15 (9.8%) cases of the follicular variant were noted. Multicentric tumors were found in 37 (24.2%) patients, of whom 12 (7.8%) had more than one PTMC on the same side and 25 (16.3%) displayed bilateral PTMC. Results: The proportions of capsular invasion and lymph node metastasis were 11.8% (18/153) and 48.1% (39/81), respectively. One patient showed distant metastasis during follow-up and died fifteen months after the operation. PTMC showed a high incidence of multifocality and lymph node metastasis in the level VI central compartment. The optimal surgical strategy for PTMC was total thyroidectomy and central compartment node dissection. Conclusions : Frozen tissue sections should be made for the prompt diagnosis of PTMC in all the thyroid nodules, except when the malignant diagnosis was already confirmed by cytology.